Measurements of the top quark branching ratios into channels with leptons and quarks with the ATLAS detector - Alconada Verzini, María Josefina (2015)
Measurements of the branching ratios of top quark decays into leptons and jets using events with tt (top antitop) pairs are reported. Events were recorded with the ATLAS detector at the LHC in pp collisions at a center-of-mass energy of 7 TeV. The collected data sample corresponds to an integrated luminosity of 4.6 fb-1. The measured top quark branching ratios agree with the Standard Model predictions within the measurement uncertainties of a few percent.